Assessment Design Plan in the Merdeka Belajar Curriculum for Islamic Religious Education - Farida Wardah Yudela; Alamsyah, Peri; Romadhon, Ahmad; Bashith, Abdul (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2025)
This study aims to explore assessment within the Merdeka Belajar Curriculum's context, particularly in Islamic Religious Education (PAI). Utilizing a literature review method and a descriptive qualitative approach, this research aims to understand how assessment measures are employed within the Merdeka Belajar Curriculum. The emphasized adaptive and responsive approach in Merdeka Belajar Curriculum assessments provides opportunities for teachers to comprehend the individual needs and abilities of students. Through three types of assessments, namely, diagnostic, formative, and summative, teachers can utilize each assessment according to the goals and information they seek to acquire.